2018
DOI: 10.3892/ijmm.2018.3813
|View full text |Cite
|
Sign up to set email alerts
|

TREK‑TRAAK two‑pore domain potassium channels protect human retinal pigment epithelium cells from oxidative stress

Abstract: The aim of the current study was to explore the potential of TREK-TRAAK two-pore domain potassium (K2P) channels in protecting human retinal pigment epithelium (hRPE) cells against oxidative stress. hRPE cells were obtained from donors, and then cell identification and detection of the expression levels of TREK-TRAAK K2P channels in hRPE cells were conducted. Subsequently, tert-butyl hydroperoxide (t-BH) was used to induce oxidative stress in hRPE cells. Docosahexaenoic acid (DHA) was used to stimulate and flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
1
Order By: Relevance
“…Fluoxetine is a small molecule that mimics neurotrophic signalling (31). One study showed that fluoxetine has a protective effect on retinal epithelial cells (32). Other studies have shown that fluoxetine promotes the recovery of synaptic proteins in the visual cortex (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine is a small molecule that mimics neurotrophic signalling (31). One study showed that fluoxetine has a protective effect on retinal epithelial cells (32). Other studies have shown that fluoxetine promotes the recovery of synaptic proteins in the visual cortex (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…At last, all of the RPE cells were co-stained with annexin V and PI to record the fluorescence intensity. 78 …”
Section: Methodsmentioning
confidence: 99%
“…Mean intensity fluorescence was measured with a green laser (430 nm) while using Flow Cytometer Guava easyCyte (Merck Millipore, Darmstadt, Germany). Incubations with only secondary antibody were used as the negative controls [47].…”
Section: Methodsmentioning
confidence: 99%